Estimation of Chronological Age from Postmortem Tissues Based on Amino Acid Racemization - GÖREN, MEHMET ZAFER; TURAN YURTSEVER, NURŞEN; TIPLAMAZ, SITKI (WILEY, 2018)
Skin and cartilage tissue specimens from 32 male and 13 female corpses aged between 17 and 50years were collected within 24h after the death. Each specimen was analyzed for the composition of dextro (D) and levo (L) forms of aspartate, glutamate, and alanine. Linear regression models were constructed using ln [(1+D/L)/(1-D/L] equationto define the relationship between the extent of racemization and the chronological age. Aspartate D/L rates from cartilage showed high correlation (r=0.779, p<0.001, n=45). Aspartate D/L rates from skin showed very low correlation (r=0.356, p<0.002, n=44). The multilinear regression model of both aspartate D/L rates of cartilage and skin tissues in 44 cases yielded a coefficient of r=0.828 (p<0.001). In conclusion, only racemization rate of Aspartate both in the skin and the cartilage tissues correlated with the chronological age. Our results may imply that the age can be estimated more precisely if two different tissue specimens are obtained from one corpse.
Keywords: forensic science; racemization; D-aspartate; L-aspartate; cartilage; skin; ASPARTIC-ACID; MARKED LONGEVITY; ELASTIC FIBERS; RIB CARTILAGE; BONE; PROTEINS; ALANINE; DEATH; RADIOCARBON; PEPTIDES